PELANGGARAN MAXIM DALAM FILM “FANTASTIC BEASTS: AND WHERE TO FIND THEM” - Erdayani, Erdayani; Ambalegin, Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2022)
This descriptive qualitative research purposed at finding the types of flouting maxims uttered by the characters in Fantastic Beasts: and Where to Find Them movie. The data were taken from the utterances contained flouting maxims in the movie. The cooperative principle theory by (Grice, 1975) conducted for analyzing the types of flouting maxims. Observational method and non-participatory technique implemented for collecting the data. Furthermore, pragmatic identity method and pragmatic competence- in equalizing technique employed for analyzing the data. The findings revealed that there were 15 utterances contained flouting maxims uttered by the characters in the movie. There were 9 data of flouting maxim of quantity, 1 data of flouting maxim of relation, 4 data of flouting maxim of relation, and 1 data of flouting maxim of manner. Flouting maxim of quantity became the most uttered because the characters frequently flouted the maxim of quantity in the movie.